Investigating the ecological and toxicological significance of Cyanox®53 recovered from intertidal sediments and varnish clam - Renkers, Stephanie L.; Bendell, Leah I. (Frontiers in Environmental Science, 2024)
We examined the ecological and toxicological implications of the microplastic, Cyanox®53, found in sediments and varnish clams across seven beaches in Burrard Inlet, British Columbia (BC). Using the simulation models embedded within Estimation Programs Interface (EPI) Suite TM , the potential persistence, bioaccumulation, and toxicity of Cyanox®53 was assessed to evaluate the risk to varnish clams foraging on sediment containing this contaminant. Moreover, we used a bioenergetic model, based on the blue-listed surf scoter species, to estimate the risk of daily ingestion of Cyanox®53 per body weight in overwintering seabirds. Our findings indicate that varnish clams collected from Burrard Inlet accumulate on average 0.46 particles of Cyanox®53/clam, and based on bioenergetic modeling, results in surf scoters potentially consuming 78 (for males) to 83 (for females) pieces of Cyanox®53 daily from foraged varnish clams. EPI Suite TM predicted Cyanox®53 to be persistent, however, unlikely to bioaccumulate as a "traditional" chemical. Furthermore, the estimation of potential acute and chronic toxicity of Cyanox®53 to aquatic organism surrogates, such as fish, Daphnia magna, and green algae, was inconclusive due to model variability and limitations within EPI Suite TM . To fully understand the potential risks of Cyanox®53 further investigation is warranted.